Stable silanone with a three-coordinate silicon atom: a century-long wait is over - Sen, Sakya S. (Angewandte Chemie-International Edition, 2014)
Keywords: cations; germanones; Ketones; silanones; transition metals

Stepwise isolation of low-valent, low-coordinate Sn and Pb mono- and dications in the coordination sphere of platinum - Braunschweig, Holger; Celik, Mehmet Ali; Dewhurst, Rian D.; Heid, Magdalena; Hupp, Florian; Sen, Sakya S. (Chemical Science, 2015)
Synthetic access to low-coordinate Pb mono- and dications is in general impeded due to their poor solubility and highly electrophilic nature. However, the electrophilicity of these cations can be tamed by attaching them to electron-rich transition metals. Following this principle we have isolated low-valent Pb mono- ([(Cy3P)(2)Pt-PbCl](2)[AlCl4](2), 8a) and dications ([(Cy3P)(2)Pt(Pb)][AlCl4](2), 11) in the coordination sphere of platinum. The same approach then has been implemented for the isolation of analogous low-valent Sn mono- (7a) and dications (10). An energy decomposition analysis (EDA-NOCV) was performed to investigate the nature of Pt-Pb and Pb-Cl bonding in [(Cy3P)(2)Pt(PbCl2)] (2), 8a and 11. The results show that the Pt-Pb bonds in 8a and 11 are electron-sharing in nature, whereas that of the precursor 2 is a dative bond. The breakdown of attractive interactions in 2, 8a and 11 reveals that the ionic interactions in the analyzed Pt-Pb and Pb-Cl bonds are always stronger than the covalent interactions, except for the Pb-Cl bond in 8a. The calculated D3 dispersion energies show that dispersion interactions play a key role in the thermodynamic stability of 2, 8a and 11.

Silanetriols and aluminosilicates - Sen, Sakya S.; Roesky, Herbert W. (Efficient methods for preparing silicon compounds, 2016)

Synthesis of silicon(II) compounds and their reactions - Sen, Sakya S.; Roesky, Herbert W. (Efficient methods for preparing silicon compounds, 2016)

Strikingly diverse reactivity of structurally identical silylene and stannylene - Parvin, Nasrina; Dasgupta, Rajarshi; Pal, Shiv; Sen, Sakya S.; Khan, Shabana (Dalton Transactions, 2017)
The reactivity of structurally identical silylene and stannylene [PhC(NtBu)(2)EN(SiMe3)(2)] (E = Si (1) and Sn (2)) towards coinage metals has been explored. While 1 has the propensity to form an adduct with coinage metals (4 and 5), 2 undergoes a ligand exchange reaction with copper halides and silver triflate leading to PhC(NtBu) 2SnX (X = Br (6), Cl (7), and OSO2CF3 (8)) with concomitant formation of [M{N(SiMe3) (2)}] (M = Cu, Ag). However, with AgSbF6 both 1 and 2 led to ion pairs, 9(+) .SbF(6)(-)and 10(+) . SbF(6)(-)displaying weaker Ag center dot center dot center dot center dot F interactions in the latter.

Silicon-fluorine chemistry: from the preparation of SiF2 to C-F bond activation using silylenes and its heavier congeners - Sen, Sakya S.; Roesky, Herbert W. (Chemical Communications, 2018)
This feature article is intended to provide a background to the history of the isolation of silicon(II) fluorides and the different synthetic methodologies used to generate them. Although first detected in the 1970s, the chemistry of silicon(II) fluorides has not encountered serious research efforts for a rather long period of time. This is somewhat surprising given the fact that the chemistry of compounds with divalent silicon has undergone a renaissance during last three decades. Recently, the interest in silicon(II) fluorides have been resparked with tremendous progress being achieved in this area, in particular, with respect to their synthesis and structural characterisation. The successful isolation of cyclic alkyl amino carbene (cAAC) stabilized silicon difluoride has completed the classic progression of SiF2, from a transient intermediate to spectroscopically detected molecule to a stable compound. The related germanium(II), tin(II), and lead(II) fluoride chemistry will also be discussed. Apart from the isolation of tetrel(II) fluorides, the use of compounds with low valent group 14 elements for the selective activation and functionalisation of C-F bonds has witnessed some remarkable advances, which will also be summarized in this feature article.

Saturated N-heterocyclic carbene based thiele's hydrocarbon with a tetrafluorophenylene linker - Kundu, Gargi; De, Sriman; Tothadi, Srinu; Das, Abhishek; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2019)
The synthesis of a SIPr [1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] derived Kekule diradicaloid with a tetrafluorophenylene spacer (3) has been described. Two synthetic routes have been reported to access 3. The cleavage of C-F bond of C6F6 by SIPr in the presence of BF3 led to double C-F activated compound with two tetrafluoro borate counter anions (2), which upon reduction by lithium metal afforded 3. Alternatively, 3 can be directly accessed in one step by reacting SIPr with C6F6 in presence of Mg metal. Compounds 2 and 3 were well characterized spectroscopically and by single-crystal X-ray diffraction studies. Experimental and computational studies support the cumulenic closed-shell singlet state of 3 with a singlet-triplet energy gap (Delta ES-T) of 23.7 kcal mol(-1).
Keywords: C-F activation; Density functional calculations; fluorine; Kekule diradicaloids; saturated NHC

Silylene induced cooperative B-H bond activation and unprecedented aldehyde C-H bond splitting with amidinate ring expansion - Swamy, V. S. V. S. N.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S.; Roesky, Herbert W. (Chemical Communications, 2019)
The addition of HBpin to PhC(NtBu)(2)SiN(SiMe3)(2) (1) results in the cleavage of the B-H bond in a cooperative fashion across the Si and amidinate-C sites. The reaction of 1 with benzaldehyde led to C-H bond activation with amidinate ring expansion leading to a five-membered heterocycle. In case of 4-fluorobenzaldehyde, a C-C bond coupling takes place leading to a dioxasilolane derivative as the major product.

Synthesis and reactivity of a hypersilylsilylene - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Inorganic chemistry, 2019)
Stabilization of an amidinatosilylene with a bulky tris(trimethylsilyl)silyl substituent was realized with the preparation of PhC(NtBu)(2)Si{Si(SiMe3)(3)} (1) from PhC(NtBu)(2)SiHCl2 with K{Si(SiMe3)(3)} in more than 90% yield. The highly deshielded Si-29 NMR resonance (delta = 76.91 ppm) can be attributed to the absence of a pi-donating substituent. The molecular structure of 1 shows a trigonal-planar geometry around the Si-II center with a Si-II-Si-IV bond length of 2.4339(13) angstrom. A series of reactions of 1 with Me3NO, S, Se, and Te were performed. While siloxane derivatives (2 and 3) are obtained from reactions with Me3NO, silachalcogenones (4-6) are formed with other chalcogens. The presence of Si=E (E = S, Se, and Te) bonds in 4-6 have been confirmed by single crystal X-ray studies. Silaoxirane (7) formation was observed when 1 was treated with acetone, demonstrating the importance of the tris(trimethylsilyl)silyl group to kinetically and thermodynamically protect the silaoxirane derivative with less bulky substituents on the C atom.

Stepwise nucleophilic substitution to access saturated N-heterocyclic carbene haloboranes with boron-methyl bonds - Kundu, Gargi; Pahar, Sanjukta; Tothadi, Srinu; Sen, Sakya S. (Organometallics, 2020)
Compounds of boranes with N-heterocyclic carbenes are known, yet little attention has been paid to NHC compounds of boron bearing methyl and halogen moieties together. The reason can be attributed to the hazardous methyldichloroborane (MeBCl2), which ignites in air. We describe here convenient solution-phase access to SIDipp.MeBCl2 (SIDipp = 1,3-bis(2,6-diisopropylphenyl)imidazolin-2-ylidene) (3) by a salt metathesis reaction of SIDipp.BCl3 (2) with MeLi. Replacement of the chlorine atoms of 3 with stepwise addition of AgOTf led to the formation of SIDipp.MeBCl(OTf) (4) and SIDipp.MeB(OTf)2 (5). In the case of 4, all of the substituents on the boron atom are different. Subsequently, we extended our synthetic approach to the amidinate system and prepared PhC(NtBu)2B(Me)Cl (7) from the reaction of PhC(NtBu)2BCl2 (6) with MeLi.

Substrate, catalyst, and solvent: the triune nature of multitasking reagents in hydroboration and cyanosilylation - Dixit, Ruchi; Bisai, Milan Kumar; Yadav, Sandeep; Yadav, Vinita; Sen, Sakya S.; Vanka, Kumar (Organometallics, 2021)
A truly green chemical process would avoid the use of an external catalyst, while still achieving high efficiency. This has been realized in the very recent past for hydroboration, cyanosilylation, acetalization, and the aza-Michael addition, among other reactions. The current combined computational and experimental study unlocks the secret to how this highly desirable outcome is accomplished: one of the reactants in the process also acts as the catalyst. Specifically, this is shown (i) for the important hydroboration reaction, with pinacolborane (HBpin) as the hydroborating reagent and benzaldehyde, acetophenone, benzoic acid and p-methoxyphenylacetylene as the hydroborated substrates, and (ii) for cyanosilylation, with trimethylcyanosilane (TMSCN) as the cyanosilylating agent and benzaldehyde as the substrate. The mechanistic understanding thus gained has then been further exploited experimentally to bring hydroboration and cyanosilylation closer to experimental conditions in catalysis. These insights can potentially be expanded to the rapidly growing area of solvent-free and internal catalyst chemistry.

Six-membered saturated NHC-stabilized borenium cations: isolation of a cationic analogue of borinic acid - Kundu, Gargi; Balayan, Kajal; Tothadi, Srinu; Sen, Sakya S. (Inorganic Chemistry, 2022)
The reaction of six-membered saturated NHC [1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene; henceforth abbreviated as 6-SIDipp] with PhBCl2 yields a Lewis base adduct, 6-SIDipp.PhBCl2 (1), which readily undergoes nucleophilic substitution reaction with AgNO3, leading to the single (2) and double (3) substitution of both chlorides with ONO2 moieties at the boron atom. The reaction of 1 with 1 equiv of AlCl3 resulted in a borenium cation of composition [6-SIDipp.B(Ph)Cl]+ (4) with AlCl4- as the counteranion. Although borenium cations with different substituents on boron have been reported, a structurally characterized phenylchloroborenium cation remains unknown. Similarly, the reaction of 1 with triflic acid provides the first representative of a new class of borenium cations bearing one hydroxyl and one phenyl group on boron (5), a cationic analogue of borinic acid. Ph-BN H Diphenylborinic acid

Substitution at sp(3) boron of a six-membered NHC center dot BH3: convenient access to a dihydroxyborenium cation - Kundu, Gargi; Ajithkumar, V. S.; Raj, K. Vipin; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we have undertaken the synthesis and investigated the reactivity of a 6-membered saturated NHC borane adduct (1). Direct electrophilic halogenation of 1 with a stoichiometric amount of I-2 led to NHC boryl iodides, 6-SIDipp center dot BH2I (2) and 6-SIDipp center dot BHI2 (3), which were further reacted with various nucleophiles to give novel 6-SIDipp based mono and disubstituted boranes with OTf (4 and 6) or ONO2 (5 and 7) functional groups. The addition of Br-2/H2O to 1 smoothly results in a dihydroxyborenium cation (8).

Six-membered NHC stabilized monomeric zinc complexes - Gour, Kritika; Kundu, Gargi; Dash, Soumya Ranjan; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2023)
This paper describes the rare use of a 6-membered saturated N-heterocyclic carbene (NHC) known as 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene (abbreviated as 6-SI-Dipp) as a ligand in zinc chemistry. We report on the investigation of the reactions between 6-SI-Dipp and ZnX2, which resulted in a range of new monomeric 6-SIDipp center dot ZnX2 complexes (X=Et (1), Cl (2), Br (3), and I (4)). We also prepared a new NHC zinc complex where the two substituents of the zinc atom are different, 6-SIDipp center dot Zn(Et)Br (7) through the reaction of the proligand [6-SIDippH]Br with ZnEt2. We have observed that the reactions of complex 1 with sulfur and HBpin led to the removal of the ZnEt2 moiety, resulting in the formation of a C=S double bond and a B H activation product, respectively. Lastly, the reaction of 1 with five-membered NHCs led to the exchange of carbene and the formation of either 5-IDipp center dot ZnEt2 (8) or 5-SIDipp center dot ZnEt2 (9).
Keywords: Lewis adduct; NHC; X-ray diffraction; zinc

Synthesis of Si(IV)- and Ge(II)-substituted amines, hydrazone, and hydrazine from hypersilyl germylene - Ajithkumar, V. S.; Ghanwat, Pratiksha B.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2023)
This study investigates the reactivity of a hypersilyl germylene [PhC-(NtBu)(2)GeSi-(SiMe3)(3)] (1) with various organic compounds including azides, diazoalkanes, 1,2-diphenylhydrazine, and trifluoroacetophenone. The reactivity observed in these reactions is driven by the insertion of the organic fragment between a silicon and germanium bond. This leads to the formation of novel compounds, including an amine featuring three different substituents from three different elements of group 14. When reacting with Me3SiCHN2, we observed the insertion of the diazoalkane fragment in an end-on fashion into the Ge-Si bond. An analogous trend was observed in reactions with 1,2-diphenylhydrazine and trifluoroacetophenone, where the N-N and C-O fragments were inserted into the Ge-Si bond. Multinuclear NMR and single-crystal X-ray diffraction analyses were conducted to characterize the newly synthesized compounds.

Saturated NHC-stabilized borenium, boronium, hydride-bridged boron cations, and a bora-acyl chloride - Kundu, Gargi; Amrutha, P. R.; Tothadi, Srinu; Sen, Sakya S. (ORGANOMETALLICS, 2024)
Keywords: activation; BORINIUM; Chemistry

Stereodivergent sila-germylenation vs. sila-stannylenation of an internal alkyne - Ajithkumar, V. S.; Ghanwat, Pratiksha B.; Saha, Sougata; Pati, Swapan K.; Sen, Sakya S. (CHEMICAL COMMUNICATIONS, 2024)
Keywords: DIVERSE REACTIVITY; H BOND ACTIVATION; hydrides

Sila[1]ferrocenophanes with Bulky Substituents - Ajithkumar, V. S.; Bisai, Milan Kumar; Yuvaraj, K.; Gonnade, Rajesh G.; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2025)
In this study, sila[1]ferrocenophanes with sterically bulky groups such as tris(trimethylsilyl) or N-heterocyclic iminato located at the bridging silicon atom are synthesized. The reactions of silicon-bound chloride in Fe(eta 5-C5H4)2SiCl2 (1) with K[Si(SiMe3)3] and silylated N-heterocyclic imine result in sila[1]ferrocenophanes 2 and 3 with bulky silicon- and nitrogen-based substituents at the ansa-bridge via elimination of KCl and Me3SiCl. Subsequently, the reduction of 1 is attempted using 2,3,5,6-tetramethyl-1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (popularly known as Mashima reagent), which leads to the elimination of Me3SiCl and generation of 1,4-dihydropyrazine-spanned sila[1]ferrocenophanes (4). All the compounds are structurally characterized.
Keywords: ansa-bridges; ferrocenophanes; hypersilyls; Mashima reagents; N-heterocyclic imines

Synthesis of diamido N-heterocyclic imines (DAC = NH) via staudinger or reductive N-N bond cleavage approach - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
This report communicates the first examples of N-heterocyclic imines based on electrophilic diamido carbenes (DACs). While 2 is prepared by classical Staudinger synthesis, 4 is obtained via an unusual reductive N-N bond cleavage of an azine by HCl. The exocyclic C=N bond lengths in 2 and 4 are substantially shorter than those based on N-heterocyclic carbenes and cyclic (alkyl)(amino)carbene reflecting the electrophilic character of DACs.